A Novel Data Encryption Algorithm To Ensure Database Security - Sivan İbrahim; Ahmet Zengin; Selman Hızal; A. F. M. Suaib Akhter; Cevat Altunkaya (Acta Infologica)
Many people apply technologies gradually, moving towards new progress and development. Moreover, many of us utilize database systems to assist our work management; the database contains our work or personal information, which increases the risk of losing our data due to disruptive electronic attacks. As a result, protecting databases from electronic attacks and data seizures is crucial. One method of identifying data is through several algorithms so that no benefit is taken from our data during electronic attacks. In this paper, we explain a formula we created for data encryption. The data is encrypted using ASCII Code. Also, we used three keys in the main formula. Because of that formula, each data we save in the database will be encrypted. The data can be Text or numbers. And through using another coordinator with the three previous keys, we can render the data to our original style. The formula focuses on data size and recording speed so that we get the same data size as when the data is encrypted at a reasonable speed.